Gas-liquid two-phase flow measurement by combining a Coriolis flowmeter with a flow conditioner and analytical models. (15th October 2020) - Meribout, Mahmoud; Shehzad, Faisal; Kharoua, Nabil; Khezzar, Lyes
Highlights: Two-phase flow meter using a liquid–gas separator and Coriolis flow meters. Application of new model based-Hierarchical neural network. Absolute error less than 2.5% for both density and mass flow rate measurement for the whole Gas Void Fraction range. Abstract: In oil–gas fields, two phase flow measurement of liquid–gas mixture for the whole Gas Void Fraction (GVF) range remains a challenging task. Coriolis flow meter is proven to be one of the most accurate device for single phase flow measurement. However, for two phase flow metering, its accuracy gets altered for liquid continuous phase (respectively gas continuous phase) in case of GVF that exceeds 20% (respectively low GVF that is lower than 80%). This paper presents a new Coriolis-based two phase flow meter (TPFM) that uses an upstream inline flow conditioner which separates liquid (i.e. water in this paper) from gas. Each of the gas dominant phase and liquid dominant phase are carried by two outlets, namely gas and liquid outlets respectively. A Coriolis flow meter and an actuated valve are placed in each outlet to measure and regulate the GVF that passes in each line. A new measurement algorithm based on a multistage artificial neural network (ANN) and which explores the physical model of the Coriolis flow meter is also suggested. This latest combines the pressure–volume-temperature (PVT) and bubble theory models to estimate the amount of gas (respectively liquid) dissolved in the liquid phase (respectively gas phase). Experimental results that were conducted on a multiphase flow loop reveals that for the whole GVF range (i.e. 0 to 100% GVF), the absolute value of the relative error on both the mass flow rate and density does not exceed 2.5%. This suggests that the proposed TPFM can be considered as a new non-hazardous alternative for accurate two phase flow measurement.